2013
DOI: 10.1111/zsc.12039
|View full text |Cite
|
Sign up to set email alerts
|

Forest refugia and riverine barriers promote diversification in the West African pygmy shrew (Crocidura obscurior complex, Soricomorpha)

Abstract: The Crocidura obscurior or West African pygmy shrew complex is endemic to West African forests from south‐eastern Guinea, eastern Liberia, southern Côte d'Ivoire and south‐western Ghana. We explore the genetic and morphometric diversity of 239 individuals of the C. obscurior complex from 17 localities across its geographical range. Using genetic data from three mitochondrial (16S, cytochrome b and COI) and four nuclear markers (BRCA1, STAT5A, HDAC2 and RIOK3) and skull geometric morphometrics, we show that thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 92 publications
(100 reference statements)
4
33
0
1
Order By: Relevance
“…longipes)? A similar pattern, with several highly overlapping sister lineages, was previously observed in other Upper Guinean small mammals (Bohoussou et al, 2015;Jacquet et al, 2014;Nicolas, Bryja, et al, 2008). The…”
supporting
confidence: 83%
See 2 more Smart Citations
“…longipes)? A similar pattern, with several highly overlapping sister lineages, was previously observed in other Upper Guinean small mammals (Bohoussou et al, 2015;Jacquet et al, 2014;Nicolas, Bryja, et al, 2008). The…”
supporting
confidence: 83%
“…More genetic data at the genomic scale, as well as quantified morphometric data including genetically identified specimens, are necessary to further assess their taxonomical status. Several recent studies showed the power of morphometric geometric approaches to discriminate cryptic shrew species and to associate a genetic lineage to a type specimen (Jacquet et al., , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Jacquet et al . ), a denser sampling is required to allow the proper testing of biogeographic scenarios (including ecological and demographic data) in African common pangolins.…”
Section: Discussionmentioning
confidence: 99%
“…; Jacquet et al . ). Nevertheless, the delimitation of ‘universal’ rainforest refugia remains difficult to establish because of the cyclic, superimposed nature of rainforest contractions through time and the likely different responses of organisms to a same series of climatic changes (Lowe et al .…”
Section: Introductionmentioning
confidence: 97%